Interpersonal Communication Strategies Between Supervisors and Subordinates to Improve Operational Performance - Sumardi Sumardi; Yoyoh Hereyah; Santa Lorita Simamora; Afdal Makkuraga (International Journal Labs, 2025)
This study examines the implementation of interpersonal communication strategies between superiors and subordinates in the operational context of PT Bukit Makmur Mandiri Utama (BUMA) Jobsite IPR. The main focus is directed at how communication interactions shape work relationships and influence the process of achieving production targets. Using a qualitative descriptive approach and case study method, this study explores the experiences, perceptions, and communication practices that occur in the field. The findings indicate that open, empathetic, and trust-based communication is an important foundation in building work synergy. However, there are a number of communication barriers that arise, such as differences in perception, incongruent communication styles, and limited time and space for interaction, technical disruptions caused by disrupted radio or internet signals, which ultimately pose real challenges in accelerating work, errors in execution, and ultimately disrupt work productivity. This study recommends the need to strengthen interpersonal communication capacity through training and continuous evaluation of internal communication systems.